Organized Crime in Kosovo: A Comprehensive Analysis of Narcotics and Human Trafficking (2019-2023) - Daci, Greta (European Scientific Journal, ESJ, 2024)
Organized crime poses an imminent threat in our society, driven by the pursuit of rapid wealth and power. The path to amassing large profits in a short time leads to various criminal activities, such as drug trafficking, human trafficking, and counterfeit goods, reaching global levels. This research is about the Republic of Kosovo. The intent is to analyze organized crime from 2019 to 2023, taking a comprehensive interest in drugs and human trafficking. Post-war countries struggle with extensive criminal networks that cause internal turmoil. Fostering criminal cooperation and combating corruption while ensuring security and safety remain significant internal issues. Its favorable location along the Balkan route is a pathway to illicit activities driven by criminal groups, with Europe as a destination. Additionally, by using a mixed-method approach combining qualitative and quantitative research through document analysis, data analysis, and statistical examination, the research offers a holistic perspective on the changes over the years, emphasizing key enforcement challenges. It also uncovers how criminal networks take advantage of security challenges and legislative gaps to operate freely. The research concludes that stricter enforcement laws and intensified anti-corruption efforts are urgently required. Improving security policies and practices, focusing on greater collaboration with other Balkan countries, enhancing border control, and tightening oversight in northern Kosovo are also priorities. Implementing the proposed measures would enhance Kosovo’s fight against organized crime and serve as a combat model for other Balkan countries.